If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
y = 23*(6/7)+6 // - 23*(6/7)+6
y-(23*(6/7))-6 = 0
y-138/7-6 = 0
y-180/7 = 0 // + 180/7
y = 180/7
y = 180/7
| 4/8=6/m | | 9(-2)+(-28/7)^3-5 | | 24/4=x/6 | | y=-0.25x^2+3*x | | 0.8(4+5)=4(0.5-2) | | 3q-2=6q+4 | | -11=7x-6(3x+11) | | b=c(1+rt) | | 3/8x-1/6=5/8x-2/3 | | -32+w=-54 | | 8(p+4q)= | | -13+w=23 | | -1/4=x/5 | | 9x+50=200 | | 78=32.2t+18 | | W+32=-54 | | w-9=1 | | 1/5x1/3 | | 3(x-8)=5x+7 | | -6x+1=-9x+7 | | 6c^2=16+20c | | 5.3X-0.86=1.06-4.3X | | 8w=80 | | x/4-2/3=8 | | 29x+81=23 | | 5y=7y-10 | | x(-8)= | | k^2=4k-11 | | 4(2x+2)=24 | | 5(2m-3)= | | 2(3h-1)+4h=10(2-3h+38h) | | 2/3+4Y=8Y-2/15 |